Penyuluhan Edukasi Fisioterapi dalam Meningkatkan Kesadaran Posisi Kerja Ergonomic dan Latihan Mandiri untuk Mengurangi Nyeri Punggung Bawah pada Pekerja di Dinas Pendidikan dan Kebudayaan Kabupaten Kutai Barat - Hendrawan T.; Atika Yulianti (Rena Cipta Mandiri, 2025)
Introduction: Prolonged sitting that leads to minimal body movement can result in various health issues for workers, one of which is the potential occurrence of musculoskeletal disorders (MSDs), such as musculoskeletal disturbances in the lower back. Sitting for extended periods can lead to health problems like lower back pain because the human body should remain dynamic and in continuous movement. Objective: This outreach program aims to enhance workers' knowledge and understanding of ergonomic work positioning and self-exercises that can be performed both at the workplace and at home, particularly in cases of low back pain (LBP). Method: The method applied involves providing educational outreach on ergonomic work positioning awareness and self-exercises, such as stretching, that workers can perform at both the workplace and at home. The promotional media used for this program includes PowerPoint presentations (PPT) and Poster. Conclusion: Based on the educational outreach activities regarding physiotherapy health and safety (OHS) and ergonomics conducted on March 13, 2025, at the Education and Culture Office of West Kutai Regency, it can be concluded that there was an increase in knowledge regarding ergonomic work positioning awareness and self-exercises, such as stretching, that workers can perform at the workplace and at home to reduce lower back pain among employees at the Education and Culture Office of West Kutai Regency.